مباني قلعة الجزائر العثمانية ( دراسة تاريخية أثرية) - بورابـة, لطـيفة (Sciences de l'Homme et de la Société; Vol. 11 (2014): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2014)
تتناول هذه الدراسة معلمًا أثريًا من أهم الآثار العثمانية في مدينة الجزائر، ويتمثل في قلعة الجزائر ومبانيها. يعود تاريخ بنائها إلى سنة 1516م. وقد اكتسبت أهمية خاصة بعد سنة (1232هـ/ 1816م)، لأن الداي علي باشا قرّر نقل مقر الحكم من دار الجنينة التي كانت مقرًا للديوان إلى القلعة، وقد تم ذلك ليلاً، وبمساعدة بعض أهالي المدينة. لذلك من الضروري أن نبدأ هذه الدراسة بإعطاء لمحة تاريخية عن تطور مدينة الجزائر، وقلعتها منذ دخول العثمانيين إليها، إلى غاية الاحتلال الفرنسي.   This study presents one of the most important Ottoman monuments in Algiers which is El Kasbah castle. The castle was constructed in 1516 AD by Uruς Barbaros. It gained more importance since 1816 AD when Ali pasha decided to transfer the government headquarters from Djenina palace to the castle. This change was carried out at night with the help of some locals. This castle didn’t attract only the historians, but it attracted also many French architects and doctors, because of its architectural and civilizational advantages it gained throughout its history. Therefore, it is essential that we begin this study by giving a historical overview of the evolution of the city of Algiers, and the castle since the entry to the Ottomans, until the French occupation.